2008
DOI: 10.1002/pola.22755
|View full text |Cite
|
Sign up to set email alerts
|

A novel type of optically active helical polymers: Synthesis and characterization of poly(N‐propargylureas)

Abstract: This article presents two novel artificial helical polymers, substituted polyacetylenes with urea groups in side chains. Poly(4) and poly(5) can be obtained in high yields (≥97%) and with moderate molecular weights (11,000–14,000). Poly(4) contains chiral centers in side chains, and poly(5) is an achiral polymer. Both of the two polymers adopted helical structures under certain conditions. More interestingly, poly(4) exhibited large specific optical rotations, resulting from the predominant one‐handed screw se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
77
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 55 publications
9
77
1
Order By: Relevance
“…The lacking of ordered helical conformations in the currently studied poly(N -propargylthiourea)s is assumed to be originated in the two -N-H groups of poly(4) in the pendant chains. Both the two -N-H groups may participate in a three-dimensional hydrogen bonding with the sulfur in the neighboring C=S groups [35]. Similar situation was observed in earlier poly(N -propargylurea)s with similar molecular structures [26].…”
Section: Uv-vis Spectrum Of M4 and Poly(4)supporting
confidence: 63%
See 1 more Smart Citation
“…The lacking of ordered helical conformations in the currently studied poly(N -propargylthiourea)s is assumed to be originated in the two -N-H groups of poly(4) in the pendant chains. Both the two -N-H groups may participate in a three-dimensional hydrogen bonding with the sulfur in the neighboring C=S groups [35]. Similar situation was observed in earlier poly(N -propargylurea)s with similar molecular structures [26].…”
Section: Uv-vis Spectrum Of M4 and Poly(4)supporting
confidence: 63%
“…The results with respect to UV-Vis absorption spectra are similar to some mono-substituted polyacetylenes studied by us earlier, e.g., poly(N -propargylsulfamide)s [34] and poly(N -propargylurea)s [26]. However, under the investigated conditions, the present poly(N -propargylthiourea)s failed to form helical conformations, which were frequently observed in mono-substituted polyacetylenes [23][24][25]35]. The lacking of ordered helical conformations in the currently studied poly(N -propargylthiourea)s is assumed to be originated in the two -N-H groups of poly(4) in the pendant chains.…”
Section: Uv-vis Spectrum Of M4 and Poly(4)supporting
confidence: 56%
“…In addition, we examined the helix inversion behavior in only water-DMF mixture; however, we found even in the system with water-DMF = 0.5:9.5 (v/v), poly 1 (taken as example) remarkably the method reported by us earlier. [ 8 ] For poly 1 emulsion, the CD spectrum showed a CD signal with negative sign at ≈ 325 nm, while the corresponding polymer solution showed a CD signal with positive sign at ≈ 350 nm. Poly 2 gave similar effects with the exception of the sign of the CD signals.…”
Section: Synthesis Of Polymer Emulsionmentioning
confidence: 98%
“…We also designed and synthesized a series of helically substituted polyacetylenes. [9][10][11][12][13][14] In the course of our research, we found that a large part of the substituted polyacetylenes in particular with bulky pendent groups are poor in solubility. Some helical polyacetylenes loose the helical conformation under varied conditions, especially at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%